A Reputation versus Prioritization Trade-Off: Unpacking Allied Perceptions of US Extended Deterrence in Distant Regions. (20th October 2021) - Kim, Tongfi; Simón, Luis
Abstract: Under what circumstances is a protégé likely to perceive its patron's extended deterrence commitments in another region as positive or negative for its own security? Protégés from distant regions see complementary reputational links between the credibility of a patron's extended deterrence commitments in each other's region. However, they are in a competitive relationship when it comes to the allocation of the patron's resources. We call this the reputation versus prioritization trade-off. We argue that whether protégés assign more importance to their patron's reputation or to being prioritized by said patron is a function of their dynamic perceptions of their regional security environment. These are, in turn, determined by their perception of their patron's resource constraints and the threat posed by an adversary. To test our argument, we examine how Japan has perceived America's evolving security commitment in Europe and how Poland has perceived the evolving US commitment in Asia.